When Digital Transformation Fails: Evidence from Rural Banking and the Rise of Compliance-Driven Digitalization - Siringoringo, Monang; Simatupang, Batara Maju; Budhijana, Bambang; Pracoyo, Antyo (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
Digital transformation is widely regarded as a key driver of competitiveness and governance in the banking sector. However, empirical evidence from smaller financial institutions remains inconsistent. This study investigates why digital transformation fails to improve governance and competitiveness in rural banking institutions (BPR/BPRS). Drawing on the Resource-Based View (RBV), Dynamic Capability Theory, and Institutional Theory, digital transformation is conceptualized as a multidimensional construct comprising core banking systems, integrated channeling systems, and reporting systems (Bharadwaj et al., 2013; Verhoef et al., 2021). Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that digital transformation does not significantly influence governance or competitiveness. Furthermore, human capital does not moderate these relationships. These findings challenge the dominant assumption that digitalization inherently enhances organizational performance (Vial, 2019). Instead, this study introduces the concept of compliance-driven digitalization, where technology adoption is driven by regulatory pressure rather than strategic intent. This study contributes by providing a failure-based explanation of digital transformation in emerging financial systems.